A Hybrid Acoustic-Wave Resonator and Lumped-Element Ladder Filter - Wagner, Michael; Gossmann, Timo; Tomasik, Jakob; Weigel, Robert; Hagelauer, Amelie Marietta; Leuschner, Stephan (IEEE International Ultrasonics Symposium, IUS, 2018)
RF frequency filters employing acoustic-wave resonators are used in common modern handsets for mobile communication. These resonators make use of the piezoelectric effect, i.e. their characteristics therefore strongly depend on employed materials and technology and comprise relatively fixed behavior. Classic filter design theory, however, is dealing with lumped reactive elements like inductors and capacitors for the realization of any-order filter designs instead. This theoretical treatment can lead to a multitude of realizable designs which makes it in fact very generous but also complex. Furthermore, theory is well-known and resulting structures are excessively explored in practice. In this paper, a new practical approach for the combination of these two filter types, preserving their respective benefits, is presented.
Created from Fastlane, Scopus look-up